2022
DOI: 10.3389/fpsyg.2022.886015
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed Comparison of Interventions for Kinesiophobia in Individuals With Musculoskeletal Pain: Systematic Review and Network Meta-Analysis

Abstract: ObjectiveThis systematic review aims to make a mixed comparison of interventions for kinesiophobia and individuals with musculoskeletal pain.MethodsA comprehensive search strategy was conducted in the database of PubMed, MEDLINE, and Web of Science with the inclusion criteria: (1) randomized controlled design; (2) patients with musculoskeletal pain as participants; (3) treatments protocols of kinesiophobia as interventions or comparisons; (4) the score of Tampa Scale Kinesiophobia (TSK) as outcome measures. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…Accordingly, clinicians managing people with post-COVID pain should listen to the patient's history for their thoughts, feelings, and behaviors that indicate either fear of movement, rumination, magnification of the threat value of pain, or a sense of helplessness. Treatments, including cognitive behavioral interventions, are recommended for the management of kinesiophobia caused by musculoskeletal pain; however, psychological interventions, such as coping strategies, are also potentially applicable [58]. Kamonseki et al reported that manual therapy strategies could also be equally effective as other cognitive interventions for managing cognitive maladaptative behaviors such as fear avoidance, kinesiophobia, and pain catastrophizing, again, in people with musculoskeletal pain conditions [59].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, clinicians managing people with post-COVID pain should listen to the patient's history for their thoughts, feelings, and behaviors that indicate either fear of movement, rumination, magnification of the threat value of pain, or a sense of helplessness. Treatments, including cognitive behavioral interventions, are recommended for the management of kinesiophobia caused by musculoskeletal pain; however, psychological interventions, such as coping strategies, are also potentially applicable [58]. Kamonseki et al reported that manual therapy strategies could also be equally effective as other cognitive interventions for managing cognitive maladaptative behaviors such as fear avoidance, kinesiophobia, and pain catastrophizing, again, in people with musculoskeletal pain conditions [59].…”
Section: Discussionmentioning
confidence: 99%
“… 59 This is supported by the results of a recent network meta-analysis that showed that the use of general exercises to keep individuals active may be inappropriate in the presence of kinesiophobia induced by musculoskeletal pain. 60 …”
Section: Discussionmentioning
confidence: 99%
“…27 Suer et al, Huang et al, and Watson et al agreed with the finding that that kinesiophobia is an excellent specific psychological tool to assess for the readiness to return to sports in athletes. [31][32][33] The PCS is used to assess the magnitude of pain catastrophizing thoughts (exaggeration of the negative threat value of pain) one engages in and was originally developed for the general population experiencing chronic pain. 28 Total scores range from 0 to 52 with a higher number indicating a greater pain catastrophizing tendency.…”
Section: Fear-avoidance Kinesiophobia and Pain Catastrophizingmentioning
confidence: 99%